Patient Satisfaction and Perception with Digital Complete Dentures Compared to Conventional Complete Dentures—A Pilot Study - Andrea Bors; Melinda Szekely; Liana Beresescu; Alexandra Maier; Felicia Beresescu (Dentistry Journal)
Background: Patient satisfaction is a critical outcome in the rehabilitation of edentulous patients. While conventional fabrication methods are widely used, digital workflows are emerging as viable alternatives. However, direct comparative evidence from the patient’s perspective remains limited. Objective: To compare patient satisfaction between conventional complete dentures (C-CD) and digital complete dentures (D-CD) in maxillary edentulous patients, including changes in perceptions over time and final prosthesis preference. Methods: A prospective, randomized crossover clinical trial was conducted in 2023–2024 involving 40 completely maxillary edentulous patients meeting specific inclusion criteria. Participants were randomly allocated into two sequence groups: Group 1 (n = 20) received C-CD first, and Group 2 (n = 20) received D-CD first, each for 6 months (T1), followed by crossover to the alternate denture for another 6 months (T2). Patient satisfaction was measured using a 10-item questionnaire at 6 and 12 months. Statistical analysis: Wilcoxon signed-rank tests were used for within-subject comparisons of denture types, and Mann–Whitney U tests for between-group comparisons, with significance set at p ≤ 0.05. Results: Using the paired crossover analysis, D-CD showed significantly better comfort than C-CD (p < 0.05). D-CD scored significantly higher than C-CD in most satisfaction domains, including comfort, retention, speech, esthetics, and need for adjustments (p ≤ 0.05). Median scores for retention, speech, esthetics, and other domains were slightly higher with D-CD but did not reach statistical significance (p > 0.05). Additionally, the D-CD required fewer post-insertion adjustment visits than the C-CD (p < 0.05). By the end of the trial, 28 patients (70%) preferred the digital denture as their final prosthesis, whereas 12 patients (30%) preferred the conventional denture. Conclusions: Incorporating digital technology in the fabrication of complete dentures significantly enhances patient satisfaction compared to conventional methods. This study highlights the clinical relevance of modern dental prosthesis technology and supports the wider integration of digital workflows. Within the limitations of this pilot study, digitally fabricated complete dentures provided overall patient satisfaction comparable to conventional dentures, with the D-CD offering a notable improvement in comfort. The majority of patients ultimately favored the digital denture, supporting the clinical viability of CAD/CAM workflows.